Nos divertimos conociendo los triángulos - Melendez Huaman, Laly (2018)
This learning session, to achieve degree in elementary education, was developed with 30 boys and girls from fifth grade of elementary education at the Educational Institution "Manuel Segundo del Águila Velásquez" in the Rioja city at San Martin Region, year 2018. The learning session belongs to Mathematics Area called “We Have Fun Knowing the Triangles”. The session development shows the pedagogical and didactic processes area, as well as the strategies, content, bibliographic references, among others. Also, the theoric information area and the theorical content in the learning session are presented. In addition, the pedagogical support to the area, pedagogical approach, pedagogical and didactic processes, competences and capacities area are also exposed.